Correlation between early patient mobilization and length of stay and readmission among surgical cancer patients with hypoalbuminemia - Nurliah Arsam; Syamsuddin; Erwin Gidion Kristanto; Hesty Utami Ramadaniaty (Physical Therapy Journal of Indonesia, 2026)
Background: Early mobilization is an important component of postoperative care and a commonly used indicator of patient prognosis. Postoperative complications, prolonged length of stay, and hospital readmission are common after cancer surgery. The purpose of this study was to evaluate the relationship between early mobilization in hypoalbuminemia cancer patients and length of stay and readmission after surgery. Methods: We conducted a retrospective cohort study with total sampling of eligible cancer patients treated at Prof. Dr. R.D Kandou General Hospital. Patients were categorized based on initiation of postoperative early mobilization. The main outcomes were prolonged length of stay (LOS > 10 days) and 30-day readmission. Results: Thirty-four patients met inclusion criteria, with 52.94% receiving early mobilization. Prolonged hospitalization was frequent, affecting 88.88% of patients, and one-third required readmission within 30 days. No significant association was found between early mobilization and either length of stay or readmission. Conclusion: Although early mobilization did not show measurable benefits in these outcomes, lack of statistical association does not imply clinical irrelevance. Early mobilization therefore remains clinically justified, not as a guarantee of shorter hospitalization, but as a strategy to preserve functional independence and mitigate the physiological costs of immobility.